Diseño conceptual y básico de una válvula bidireccional anti-retorno (Check Valve) (2020)
Conceptual and basic design of a valve that allows the change of direction of a gate system that prevents a fluid from returning through a pipe. Additionally, some simulations were carried out to check the viability of the project.--Taken from the Degree Document Format.